The effects of Robot-assisted gait training and virtual reality on balance and gait in stroke survivors: A randomized controlled trial - Akinci, Murat; Burak, Mustafa; Yasar, Evren; Kilic, Rabia Tugba (Elsevier Ireland Ltd, 2023)
Background: Stroke survivors often experience balance and gait problems, which can affect their quality of life and independence in daily living activities. Robot-assisted gait training, such as Lokomat with virtual reality, has been found to be effective in improving gait and balance. However, the specific effects of each virtual reality application on balance and spatiotemporal parameters of gait are not yet established. This study aims to investigate the effects of different virtual reality applications on these parameters.Research question: What are the specific effects of each Lokomat augmented performance feedback application on balance and spatiotemporal parameters of gait in stroke survivors?Methods: The study is a randomized controlled trial conducted with four groups: Control Group, Endurance Group, Attention and Motivation Group, and Activity Timing Group. All participants received six weeks of physiotherapy, and Lokomat groups had additional robot-assisted gait training with Lokomat for three days a week. The Endurance group used Lokomat with Faster, Attention and Motivation Group with Gabarello and Smile, and Activity Timing Group with Curve Pursuit, Treasures, and High Flyer applications. Various tests were used to assess walking and balance in the study (gait analysis, 6-minute walk test, 10-meter walk test, Berg Balance Scale, postural stability, and limits of stability).Results and significance: The study involved 56 male stroke survivors (mean age: 60.02 +/- 6.83 years, post-stroke time: 238.88 +/- 40.88 days). All groups improved walking speed and distance significantly, but Endurance was better (p < 0.001). Balance improved significantly in all groups, but Attention and Motivation was superior in Berg Balance Scale, postural stability, and limits of stability (p < 0.001). The selection of virtual reality appli-cations during robot-assisted gait training according to rehabilitation goals is important for successful rehabil-itation, as these applications may have varying effects on balance and walking.
Keywords: Augmented performance feedback; Lokomat; RAGT; Spatiotemporal; Stroke